Stepping strategy used to recover balance during an induced fall is associated with impaired function and strength in people with knee osteoarthritis. (20th June 2016) - Levinger, Pazit; Downie, Calum; Nagano, Hanatsu; Petersen, Aaron; Hayes, Alan; Sanders, Kerrie M.; Cicuttini, Flavia; Begg, Rezaul
Abstract: Aim: We investigated differences in function, strength and pain in those with knee osteoarthritis (OA) who responded with a single step compared to multiple steps during balance recovery during an induced forward fall. Method: The stepping response of 24 participants with knee OA (50% female, age 68.6 ± 6.2 years) as they recovered balance from an induced forward fall was recorded. Participants were grouped based on their stepping response as single‐stepper and multi‐stepper. Comparison was made between the groups for functional and strength tests and self‐reported pain, function, quality of life, fear of falls and physical activity. Results: Fourteen of the participants (58%) responded with a multiple step response. Multiple steppers demonstrated greater time for the up and go ( P = 0.01), the stair climb tests ( P = 0.05), as well as reduced distance during the 2 min walk test ( P = 0.001) and reduced isokinetic knee extension strength ( P = 0.02). Conclusion: Those who demonstrated multiple step response had impaired function, reduced strength and were less physically active. Given the high prevalence of falls in people with knee OA, further studies are required to better understand the ability of people with knee OA to respond and avoid falls.